Comparison the acute effect of moderate-intensity treadmill exercise and arm crank exercise on autonomic cardiac functions in adult male - Alsayed Abdelhameed Shanb; Enas Fawzy Youssef; Mohammad Ahsan; Raafat Mohammed Ahmed; Mahmoud Alsayed Shanab; Mohamed Yahia Abdelkhalikk (IP Iermakov S.S., 2023)
Background and Study Aim. Cardiovascular parameters testing can be used by various modalities ranging from ground running to sophisticated computerized treadmills. The purpose of this study was to compare the acute effect of treadmill moderate-intensity exercise with arm crank exercise on autonomic cardiac function among adult males. Material and Methods. One hundred-twenty male participants participated in this study. They were randomly allocated to a treadmill exercise group with sixty participants and the other sixty participants allocated into an arm crank exercise group. Both groups performed exercises for forty minutes. Autonomic cardiac functions (heart rate variability - HRV), heartbeats, and arterial blood pressure) were determined with the help of Phillips DigiTrak XT Holter heart rate monitor, Polar® Grit X watch, and automatic sphygmomanometer. An independent t-test was used to compare the anthropometric data between both groups. One-way analysis of variance was used to determine the differences between treadmill exercise and arm crank for autonomic cardiac functions among adult males. Results. The HRV decreased significantly during treadmill exercise than arm crank exercise. Mean values of heartbeats (HR), systolic blood pressure (SBP), and rate pressure product (RPP) increased significantly during both exercises. In comparison, mean values of HRV parameters were reduced more significantly during treadmill exercise than arm crank. Mean values of the HR, SBP, and RPP increased significantly during treadmill exercise than arm crank exercise. Conclusion. The study's findings suggest that treadmill exercises are responsible for a greater significant reduction in HRV. The HR, SBP, PP, and RPP significantly increased during treadmill exercises than arm crank. This study suggests that when recommending exercise to any individual, the intensity and mode of exercise are crucial.